Impacts of future climate and land use change on water yield in a semiarid basin in Iran. (4th February 2020) - Shirmohammadi, Bagher; Malekian, Arash; Salajegheh, Ali; Taheri, Bahram; Azarnivand, Hossein; Malek, Ziga; Verburg, Peter H.
Abstract: Studying the interaction between hydrology, land use, and climate change is necessary to support sustainable water resources management. It is unknown how land management interventions in dry climate conditions can benefit water yield in the context of climate and land use change interactions. In this study, we assessed the effects of both land use and predicted climate change on the Mordagh Chay basin water yield using the Integrated Valuation of Ecosystem Services and Tradeoffs model. First, we modeled the current water yield, followed by developing six combined climate–land use scenarios until 2030 based on the CCSM4 climate model for the RCP4.5 and RCP8.5 scenarios. We used three future land use scenarios simulated by the Dyna‐CLUE model. The trend scenario of land use change, which does not include any improvements in irrigation efficiency, significantly affected basin water yield under both climate scenarios. Water yield decreases by 19.8% and 31.8% for the RCP4.5 and RCP8.5, respectively. Under all land use scenarios that included improvements in irrigation efficiency, the water yield responded positively. For the RCP4.5 scenario, the water yield was projected to increase between 16.6% and 18% depending on the land use scenario. The increase in water yield under the RCP8.5 climate scenario was much lower than for the RCP4.5 scenario (about one‐third). Overall, the results showed that by adopting appropriate irrigation efficiency, it is possible to achieve a better balance between environmental needs and regional economic and agricultural development. The results provide insight into possible sustainable development options and also provide guidance for managing the other Urmia Lake sub‐basins, whereas the approach of integrated assessment of climate, land use change, and land management options is also applicable in other conditions to help inform sustainable management.